International criminalization of attacks on educational facilities during armed conflicts (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The issue of the exposure of educational facilities to attacks of all kinds is now of increasing importance, because of its prevalence in areas of armed conflicts, whether international or non-international armed conflicts. The United Nations is making great efforts to ban these attacks on more than one level. Whether by concluding international treaties and protocols to limit them, or by issuing decisions and recommendations to its various organs; All the way to ban this criminal phenomenon at the global level. Therefore, in this research, we will focus on its early roots since ancient times, up to the four Geneva Conventions of 1949, and the two Additional Protocols of 1977, where the rules and foundations governing the conduct of armed conflicts were established, including the rules for protecting civilian objects (including educational facilities, of course). the consequences of violating these rules; For example, the establishment of international criminal responsibility, which evolved from merely repairing the damage to becoming an individual criminal responsibility, the individuals who commit it are punished with the most severe penalties before the national judiciary of the concerned state, or before the international and international criminal courts that appeared at the end of the last century and the beginning of the current century, Regardless of the perpetrator's status and status (military commander - head of state - government official). Many international bodies (political-administrative-judicial) concerned with ensuring respect for these rules were established, such as some United Nations bodies and organizations, and the International Criminal Court, which had a major role in protecting human rights, including the right to education, by protecting the facilities necessary for the practice of education. During armed conflicts.